OPTIMALISASI PENERAPAN KOMPONEN LANGUAGE DAN PICTORIAL PADA PEMBELAJARAN BERKERANGKA ELPSA UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIKA SISWA KELAS IX.3 MTsN 1 BIMA - Muhdar, Muhdar (Media Pendidikan Matematika, 2019)
One of the fundamental problem of students in mathematics learning is the low mathematical communication skills. The solution  of this problem in this study was the optimization of the application of ELPSA frame  work learning with a focus on Language and Pictorial components. The  purpose of  this study was to find out and explore the effect of optimizing the application of language and pictorial components on ELPSA framework learning on mathematical communication skills. This research is a classroom action research consisting of two cycles in class IX.3 MTsN 1 Bima  for  20  students divided into three groups, 5 students to  upper  group, 5 students to  lower group  and 10 students  middle group. The results showed that the optimization of the application of  Language and  Pictorial components had an effect on the improvement of communication skills of class IX.3 MTsN 1 Bima students as indicated by observational data during learning activities. In the first cycle the average value of mathematical communication skills before the optimization activities was carried out was 49.33 and the average value of mathematical communication skills after optimization activities was 69.08 whereas in the second cycle data obtained the average communication ability before optimization activities was 53 , 42 while communication skills after the optimization activities are 71.50.